FOXP3+ regulatory T cells and the immune escape in solid tumours - Qiu, Yiran; Ke, Shouyu; Chen, Jieqiong; Qin, Zhizhen; Zhang, Wenle; Yuan, Yaqin; Meng, Dehua; Zhao, Gang; Wu, Kejin; Li, Bin; Li, Dan (Frontiers in Immunology, 2022)
FOXP3+ regulatory T (Treg) cells play critical roles in establishing the immunosuppressive tumour microenvironment, which is achieved and dynamically maintained with the contribution of various stromal and immune cell subsets. However, the dynamics of non-lymphoid FOXP3+ Treg cells and the mutual regulation of Treg cells and other cell types in solid tumour microenvironment remains largely unclear. In this review, we summarize the latest findings on the dynamic connections and reciprocal regulations of non-lymphoid Treg cell subsets in accordance with well-established and new emerging hallmarks of cancer, especially on the immune escape of tumour cells in solid tumours. Our comprehension of the interplay between FOXP3+ Treg cells and key hallmarks of cancer may provide new insights into the development of next-generation engineered T cell-based immune treatments for solid tumours.